Modafinil for the treatment of fatigue in lung cancer: results of a placebo-controlled, double-blind, randomized trial. - Spathis, A; Fife, K; Blackhall, F; Dutton, S; Bahadori, R; Wharton, R; O'Brien, M; Stone, P; Benepal, T; Bates, N; Wee, B (American Society of Clinical Oncology, 2014)
PURPOSE: Fatigue is a distressing symptom occurring in more than 60% of patients with cancer. The CNS stimulants modafinil and methylphenidate are recommended for the treatment of cancer-related fatigue, despite a limited evidence base. We aimed to evaluate the efficacy and tolerability of modafinil in the management of fatigue in patients with non-small-cell lung cancer (NSCLC). PATIENTS AND METHODS: Adults with advanced NSCLC and performance status of 0 to 2, who were not treated with chemotherapy or radiotherapy within the last 4 weeks, were randomly assigned to daily modafinil (100 mg on days 1 to 14; 200 mg on days 15 to 28) or matched placebo. The primary outcome was change in Functional Assessment of Chronic Illness Therapy (FACIT) -Fatigue score from baseline to 28 days, adjusted for baseline fatigue and performance status. Secondary outcomes included safety and patient-reported measures of depression, daytime sleepiness, and quality of life. RESULTS: A total of 208 patients were randomly assigned, and 160 patients (modafinil, n = 75; placebo, n = 85) completed questionnaires at both baseline and day 28 and were included in the modified intention-to-treat analysis. FACIT-Fatigue scores improved from baseline to day 28 (mean score change: modafinil, 5.29; 95% CI, 2.57 to 8.02; placebo, 5.09; 95% CI, 2.54 to 7.65), but there was no difference between treatments (0.20; 95% CI, -3.56 to 3.97). There was also no difference between treatments for the secondary outcomes; 47% of the modafinil group and 23% of the placebo group stated that the intervention was not helpful. CONCLUSION: Modafinil had no effect on cancer-related fatigue and should not be prescribed outside a clinical trial setting. Its use was associated with a clinically significant placebo effect.